Comparison of two multiplex immunochromatographic assays for the rapid detection of major carbapenemases in Enterobacterales. (21st February 2020) - Bogaerts, Pierre; Berger, Anne-Sophie; Evrard, Stéphanie; Huang, Te-Din
Abstract: Objectives: Two commercially available lateral flow immunochromatographic assays (ICAs) for detection of the major carbapenemases were prospectively assessed for the detection of carbapenemases in Enterobacterales: RESIST-4 O.K.N.V. (Coris BioConcept) and NG-Test CARBA 5 (NG Biotech). Methods: These two assays were performed prospectively on consecutive Enterobacterales suspected of producing a carbapenemase that were referred to the Belgian National Reference Center for Monitoring Antimicrobial Resistance in Gram-Negative Bacteria between March and June 2018. The intensity of the band corresponding to a carbapenemase for each test was compared using ImageJ software. Results: Of the 161 isolates tested, a carbapenemase was detected in 91 (60 OXA-48-like, 15 VIM, 9 KPC, 5 NDM, 1 IMP and 1 IMP + OXA-48); in the remaining 70, no carbapenemases were detected. For both tests, the results were 100% concordant with the results of the PCR-sequencing reference method. Two IMP producers were only detected by NG-Test CARBA 5 as IMP is not targeted by RESIST-4 O.K.N.V. The mean intensity of the OXA-48, VIM and NDM bands displayed by NG-Test CARBA 5 was 3 to 3.7 times higher than for RESIST-4 O.K.N.V., while the KPC band was on average 1.7 times more intense with RESIST-4 O.K.N.V. Conclusions: RESIST-4 O.K.N.V. and NG-Test CARBA 5 are two efficient assays for identification of the major carbapenemases. NG-Test CARBA 5 offers the advantage of detecting IMP, which remains rare in Western countries.